Monteiro Lobato Tradutor - Maria Augusta Hermengarda Wurthmann Ribeiro; Augustinho Aparecido Martins (Educação: Teoria e Prática, 2007)
It is the narrative of a bibliographical research on the translations of the Snow-white Story, the Grimm Brothers carried through by Monteiro Lobato and Tatiana Belinky. It focuses the importance of the translation of infantile stories in the start of twentieth century and of Monteiro Lobato in this exercise. We carry through a comparative analysis of the translations with basis in theoretical references on translation. We also approach the use of these translations as important educational tool.